Równowaga rynkowa jako rezultat działań zbiorowych i jako rezultat działań spontanicznych - Balicki, Władysław (Market equilibrium as a result of collective activities and as a result of spontaneous activities, 2005)
At the beginning the author gives reasons for the thesis that functioning of market equilibrium model assumes implicite collective activities. Proving, that consistent concluding on the ground of these assumptions leads to the institution of cartel with particular rules of functioning, is one the problems that author analyses. Next, the author presents the manipulation of assumptions’ reconstruction on the basis of two examples. Concluding on the grounds of accepted separately for buyers and sellers assumptions in market equilibrium models is the succeeding stage of his analysis. “Model without knowledge about market” in which buyers and sellers do not know a process offered by other sellers is the first step. This model helps to work out the conclusion that equilibrium price does not exist and supply is offered in segments with various prices. However, demand equalizes with supply. In the next step, the author comes to conclusion from model in which the knowledge of market is only attributed to buyers. As a result he presents a model in which the price oscillates about a chosen value that is not equilibrium price and the demand does not equalize with supply. Next, the knowledge of market is attributed as well to sellers as to buyers. The analysis leads to the conclusion that a cartel with particular rules such as: finally only one seller who had not found buyers before, dictates the price, is based on these assumptions. The author presents his own market cleaning model in the last part of the article. The model starts with the process chaos and lack of demand and supply equality in each segment and ends with equilibrium price and equality between demand and supply. An extensive numerical example explains the model. The final conclusion of the article goes as follows: equilibrium cannot be educed from the market equilibrium models which are popular in the economics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 115-130